PUBLIC SECURITY AND CRIMINAL LAW - LIMITS IN RESTRICTING THE RIGHTS OF CITIZENS - Mirić, Filip; Grbić Pavlović, Nikolina; Đorović, Ivan; Paunović, Dragan (ACADEMIC REVIEW, 2025)
The fundamental function of criminal law is to protect the most important social values from injury or endangerment. Apart from this protective role, which accompanies the public security system, on the other hand, criminal law also protects the basic rights and freedoms of citizens. This protection also applies to the public security system, both to persons deprived of their liberty and to society as a whole. The subject of the paper is the analysis of the analysys the content of laws and by-laws related to the public security system and the rights of citizens, taking into account the protective function of criminal law and its role in the system of positive law and legal sciences. From this specific subject of work, its goal also follows. Namely, the aim of this paper is to point out the importance of respecting the rights and freedoms of citizens in present legal order. This is the only true guarantee of a democratic society.